Stieleriacines, N-Acyl Dehydrotyrosines From the Marine Planctomycete Stieleria neptunia sp. nov. - Sandargo, Birthe; Jeske, Olga; Boedeker, Christian; Wiegand, Sandra; Wennrich, Jan-Peer; Kallscheuer, Nicolai; Jogler, Mareike; Rohde, Manfred; Jogler, Christian; Surup, Frank (Frontiers in Microbiology, 2020)
Bacteria of the phylum Planctomycetes occur ubiquitously in marine environments and play important roles in the marine nitrogen- and carbon cycle, for example as scavengers after phototrophic blooms. Here, we describe the isolation and characterization of the planctomycetal strain Enr13T isolated from a Posidonia sp. biofilm obtained from seawater sediment close to Panarea Island, Italy. Multilocus Sequence Analysis tree reconstruction support the phylogenetic distance of Enr13T from other cultivated Planctomycetes from the same phylogenetic cluster. HPLC-MS analysis of culture broth obtained from Enr13T revealed the presence of lipophilic metabolites, of which the major metabolite was isolated by preparative reversed-phase HPLC. The structure of this compound, named stieleriacine D (1), was elucidated utilizing HRESIMS, 1D and 2D NMR data as a new N-acylated dehydrotyrosine derivative. Its biosynthesis was proposed based on an in silico gene cluster analysis. During analysis of the MS/MS spectrum of 1 and its minor derivative 2, it was possible to assign the structure of 2 without isolation. 1 showed antibacterial activity, however, the wide distribution of structurally related compounds indicates a potential role as a signal molecule.